A cationic polymeric prodrug with chemotherapeutic self-sensibilization co-delivering MMP-9 shRNA plasmid for a combined therapy to nasopharyngeal carcinoma. (1st January 2019) - Liu, Tao; Wu, Xidong; Chen, Shaohua; Wu, Peina; Han, Hong; Zhang, Hongbin; Li, Junzheng; Li, Guanxue; Zhang, Siyi
Abstract: To obtain a high-efficiency drug and gene co-delivery system to HNE-1 tumor therapy, a polymeric prodrug (PAAs-MTX) with chemotherapeutic sensibilization was synthesized consisting of a GSH-response hyperbranched poly(amido amine) (PAAs) and an antitumor drug of methotrexate (MTX). Then, the targeting molecule to HNE-1 cells, transferrin (Tf), was conjugated to form the Tf-PAAs-MTX. This polymeric prodrug could deliver MMP-9 shRNA plasmid (pMMP-9) again to form the drug and gene co-delivery system of Tf-PAAs-MTX/pMMP-9. The co-delivery system showed the effective drug and gene delivery ability with high cytotoxicity and gene transfection efficiency to HNE-1 cells. Besides that, Tf-PAAs-MTX also showed the chemotherapeutic sensibilization effect, the formulation containing PAAs segments showed much higher cytotoxicity than that of free MTX. Benefiting from the sensibilization effect and MTX/pMMP-9 co-delivery strategy, this Tf-PAAs-MTX/pMMP-9 co-delivery system exhibited the significantly improved therapeutic efficacy to HNE-1 tumor in a combined manner which was confirmed by in vitro and in vivo assays. Moreover, its biocompatibility, especially the blood compatibility was analyzed. This polymeric prodrug provided an easily delivery system combining the drug/gene co-delivery, chemotherapeutic sensibilization and targeting into one single platform, which showed a promising application in nasopharyngeal carcinoma therapy.